Targeting Viral Ion Channels: A Promising Strategy to Curb SARS-CoV-2 - Anamika Singh; Isaiah T. Arkin (MDPI AG, 2022)
SARS-CoV-2 is the etiological agent COVID-19, one of the most impactful health crises afflicting humanity in recent decades. While research advances have yielded several treatment and prevention options, the pandemic is slow to abate, necessitating an expansion of our treatment arsenal. As a member of the coronaviridae, SARS-CoV-2 contains several ion channels, of which E and 3a are the best characterized. Since ion channels as a family are excellent drug targets, we sought to inhibit both viroporins as a means to curb infectivity. In a previous targeted study, we identified several blockers to each channel from an extensive drug repurposing library. Herein, we examined the ability of said compounds on the whole virus in cellulo. Gratifyingly, many of the blockers exhibited antiviral activity in a stringent assay examining protection from viral-driven death. In particular, darapladib and flumatinib, both 3a blockers, displayed potent antiviral activity. Furthermore, appreciable synergism between flumatinib and several E blockers was identified in a concentration regime in which the compounds are present in human plasma following oral administration. Taken together, targeting ion channels represents a promising approach to both augment and complement our antiviral arsenal against COVID-19.